“Education: The Engagement and Its Frustration”, A Comparative Analysis of Oakeshott’s and Iqbal’s Philosophies of Education Within the Paradigm of Islamic Educational Philosophy. - Dr Muhammad Iqbal Shah; Dr. Ali Raza Tahir; Muhammad Ali Muhammad Akhter Shah (Journal of Religion and Society, 2025)
Every race, civilization, culture or religion has a set of modes of behaviors and a code of ‘Do-s’ and ‘Do-nots’. Every person of that particular paradigm is demanded, if the one wants to be and remained to the member of that domain, to follow and behave according to these laws which may be written or verbal. These laws occupy the central theme of the respective framework of life and they are the vital factors of identity and continuation for survival. If any force is able to snatch the very principles from that particular group, then that will lose its identity or existence. Thus, these identity awarding laws has been name as the culture so the attack on any culture means the destruction of that respective people. Due to this grave value and it is essential to transmit the laws, values and culture to the new generations. This is possible through the medium of education. Thus, through this the newcomers not only maintain their identity but also can survive as separate people. Accordingly maintaining the cultural heritage and legacy of the meanings of the laws and its transmission to the new generation is the main objective of any philosophy of education. Here three man philosophies of education have been focused, the first is Oakeshott’s who set the goal as ‘learning to be human’ through learning the meanings of the inheritance of culture, the second is Iqbal who focused the individuality and sublimation of human values and Muslim Culture in the personification of ‘Self-hood’,‘Khudi’ or ‘Ego’ and the third one is Islamic which views education as transmission of the legacy of knowledge from Prophets and identity as being ‘Kha’s ha tar’keeb mai qwm e Rassol e Hash’mi’۔ The nexus point is that all their ones focus the welfare of human beings and have similarity of objectives in depth. Fulfilling these goals means the success of these philosophies otherwise we will frustrate them. Keywords: Culture, Ego, Frustration, Inheritance, Tradition, Welfare.